Laryngomalacia: Disease Presentation, Spectrum, and Management - April M. Landry; Dana M. Thompson (Hindawi Limited, 2012)
Laryngomalacia is the most common cause of stridor in newborns, affecting 45-75% of all infants with congenital stridor. The spectrum of disease presentation, progression, and outcomes is varied. Identifying symptoms and patient factors that influence disease severity helps predict outcomes. Findings. Infants with stridor who do not have significant feeding-related symptoms can be managed expectantly without intervention. Infants with stridor and feeding-related symptoms benefit from acid suppression treatment. Those with additional symptoms of aspiration, failure to thrive, and consequences of airway obstruction and hypoxia require surgical intervention. The presence of an additional level of airway obstruction worsens symptoms and has a 4.5x risk of requiring surgical intervention, usually supraglottoplasty. The presence of medical comorbidities predicts worse symptoms. Summary. Most with laryngomalacia will have mild-to-moderate symptoms and not require surgical intervention. Those with gastroesophageal reflux and/or laryngopharyngeal reflux have symptom improvement from acid suppression therapy. Those with severe enough disease to require supraglottoplasty will have minimal complications and good outcomes if multiple medical comorbidities are not present. Identifying patient factors that influence disease severity is an important aspect of care provided to infants with laryngomalacia.